Heterosis for seed yield in sesame (Sesamum indicum L.): Heterosis for seed yield in sesame (Sesamum indicum L.) - A DISOWJA; C PARAMESWARI; R P GNANAMALAR; S VELLAIKUMAR (Journal of Oilseeds Research, 2020)
Sesame is one of the most important oilseed crops grown in tropical regions like Africa and India. In this study a line × tester analysis was conducted using four lines and six testers to identify the best heterotic combination for seed yield. Among 24 cross combinations studied, TMV 7 × RT 127 showed the highest positive significant heterosis for seed yield, 1000 seed weight and total number of capsules.